SEATBELT USE AMONG DRUNK DRIVERS IN DIFFERENT LEGISLATIVE SETTINGS. (13th October 2014) - Adams, Scott; Cotti, Chad; Tefft, Nathan
<x xml:space="preserve">Abstract</x> We present evidence from the Fatality Analysis Reporting System and Behavioral Risk Factor Surveillance System that shows increased seatbelt use following the concurrent presence of stricter blood alcohol content thresholds and primarily enforced seatbelt laws. This suggests that inebriated drivers may use their seat belts more judiciously to avoid being identified as a drunk driver by law enforcement. The interactive effect of stricter drunk driving laws and primary seatbelt laws are also shown to be more effective than either law passed in isolation in terms of reducing traffic fatalities. (JEL K4, I18)